Preparation method of high thermal conductivity brake disc

By plating copper on the surface of SiO2 particles and mixing it with copper powder, graphite and organometallic binder, high thermal conductivity and poor wear resistance of cast iron brake discs are solved, and the effects of high thermal conductivity and long service life are achieved.

CN117431532BActive Publication Date: 2025-03-14烟台美丰机械集团有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311468928.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2025-03-14
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

The existing cast iron brake discs have low thermal conductivity, prone to thermal cracking and poor wear resistance, making it difficult to meet the safety and service life requirements of the automotive brake system.

Method used

The copper was plated on the surface of SiO2 particles by chemical electroplating and mixed with copper powder, graphite and organometallic binder. High thermal conductivity brake discs were prepared by cold press molding and vacuum hot press sintering.

Benefits of technology

It significantly improves the thermal conductivity, hardness and tensile strength of the brake disc, reduces production costs and manufacturing cycles, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of brake disc preparation, and in particular provides a method for preparing a high thermal conductivity brake disc; for the high thermal conductivity brake disc prepared by the present invention, copper plating on the surface of silicon dioxide can effectively reduce the pores at the interface between SiO2 particles and a copper matrix, and improve the interface bonding state between the silicon dioxide and the copper matrix; copper plating on the surface of SiO2 particles can further improve the hardness and tensile strength of the composite material, and has good mechanical properties; the high thermal conductivity brake disc prepared by the present invention has a thermal conductivity of up to 143W / (m·K) at 300°C, greatly improved thermal conductivity, and has significantly high thermal conductivity; the high thermal conductivity brake disc prepared by the present invention has a high metal utilization rate, a short manufacturing cycle, and a low production cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brake disc preparation, and in particular to a method for preparing a high thermal conductivity brake disc. Background Art

[0002] Brake discs are an important part of the automobile braking system, and the braking performance is directly related to the driving safety of the vehicle. The widely used cast iron brake discs have low thermal conductivity, are prone to thermal cracking, and have poor wear resistance, and need to be improved. By consulting a large amount of relevant information at home and abroad, it can be seen that replacing cast iron brake discs with light-weight, high-performance metal-based composite brake discs is the main development direction of automobile brake discs in the future. At the same time, as one of my country's pillar industries, the automobile industry has developed rapidly in recent years, and the demand for brake discs is also very huge.

[0003] Chinese patent CN116287960A: belongs to the technical field of brake disc preparation, and specifically relates to a method for preparing a high thermal conductivity brake disc. The main chemical components and their weight percentages of the high thermal conductivity brake disc described in the present invention are: carbon 3.7-4.0%, silicon 0.6-1.2%, manganese 0.6-0.8%, chromium 0.1-0.3%, boron 0.02-0.12%, and the rest are iron and inevitable impurities. The high thermal conductivity brake disc of the present invention has good thermal conductivity, high temperature strength, high temperature wear resistance and thermal fatigue resistance, which can significantly improve the safety reliability and service life of the brake disc; and its preparation method is reasonable.

[0004] Chinese patent CN116551316A: It relates to the field of titanium alloy manufacturing technology, and in particular to a manufacturing process for a high-performance titanium brake disc blank, including the following steps: S1, preparation of raw materials; S2, blank forging: S2-1, forging ingots through hot die forging press; S2-2, reversing upsetting through hot die forging press again; S2-3, upsetting through fast forging machine; S3, finished product forging; S4, heat treatment; S5, physical and chemical inspection; S6, rough machining; S7, special heat treatment; S8, finishing; S9, size inspection. High-performance annular blanks are obtained through special material ratios and hot processing technology, and the tensile strength, yield strength, elongation, and cross-sectional shrinkage indexes are significantly improved. Special heat treatment during the processing process can play the role of semi-finished product shape correction and stress elimination, and prevent deformation in later processing. During the finishing process, the contact area between the chuck and the blank is increased by a three-jaw clamp to prevent deformation due to external forces and deformation during the processing process, and improve the qualified rate.

[0005] Chinese patent CN219413340U: discloses a brake disc with good heat dissipation function, including an annular brake disc surface, wherein a plurality of first conical ribs are radially distributed in the brake disc surface with the center of the brake disc surface as the origin, the top of the first conical rib faces the outside of the brake disc surface, a second conical rib is arranged between any two adjacent first conical ribs, the top of the second conical rib faces the inside of the brake, and a V-shaped heat dissipation duct is formed between any second conical rib and the first conical ribs on both sides. The utility model is used to improve the heat dissipation effect of the brake disc in the practical process, improve the braking performance of the vehicle, and ensure the safety of the driver.

[0006] At present, most of the automobile brake discs at home and abroad are made of cast iron, which has many disadvantages: due to the limitations of the casting process, the dimensional accuracy of the casting is poor, and the entire surface of the brake disc needs to be machined; after multiple processing, the metal utilization rate is low, the manufacturing cycle is long, and the production cost is greatly increased; the thermal conductivity of cast iron brake discs is poor, and the surface temperature of cast iron brake discs can reach 60°C due to the heat generated by braking friction. The working surface temperature is very high and the temperature gradient is large, which is easy to form hot spots and cause thermal cracking. Summary of the invention

[0007] In view of this, in order to solve the above problems, the present invention provides a method for preparing a high thermal conductivity brake disc, and the operating steps are as follows:

[0008] S1: The pre-treated SiO 2 The particles are placed in 15-25 parts of disodium ethylenediaminetetraacetate, 10-15 parts of formaldehyde, 10-15 parts of copper sulfate, 10-20 parts of potassium sodium tartrate, 10-15 parts of sodium hydroxide, and 100-200 parts of deionized water, and after heating, chemical electroplating is performed;

[0009] S2: Copper-plated SiO 2 The particles are placed in an ethanol solution, stirred for 30-50 minutes, then washed with the ethanol solution several times and dried;

[0010] S3: According to weight, 70-90 parts of copper powder, 1-5 parts of copper-plated SiO 2 Particles, 1-3 parts of graphite, 3-6 parts of organic metal binder, mix for 30-60 minutes, and use a flat vulcanizer to cold press.

[0011] S4: The cold pressed green sheet is sintered in a vacuum hot pressing furnace at high temperature, and then hot pressed and cooled to obtain a high thermal conductivity brake disc.

[0012] The electroplating temperature of S1 is 30-50°C.

[0013] The electroplating time of S1 is 10-20 minutes.

[0014] The copper plating thickness of S1 is 0.3-0.5 μm.

[0015] The SiO 2 The particle pretreatment steps are:

[0016] A1: Weigh 10-20 parts of SiO 2 The particles are repeatedly washed with distilled water, and then placed in 50-80 parts of acetone solution while soaking and stirring for 30-90 minutes; then placed in 50-80 parts of 10-20% HCl solution, and continue to soak and stir for 30-90 minutes; and then repeatedly washed with distilled water;

[0017] A2: SiO 2 The particles are then placed in 50-80 parts of a 10-20% stannous chloride solution, and stirred for 10-30 minutes while being immersed; and then repeatedly washed with distilled water;

[0018] A3: SiO 2 The particles are then placed in 50-80 parts of a palladium chloride solution having a mass concentration of 0.1-0.3%, and stirred for 10-30 minutes while being immersed; then they are repeatedly washed with distilled water; and dried for later use.

[0019] The stirring rate is 500-1000 rpm.

[0020] The cold pressing pressure is 400-500 MPa and the time is 1-3 min.

[0021] The vacuum degree in the vacuum hot pressing sintering furnace is 1×10 -2 ~3x10 -2 Pa, temperature is 800-1000℃.

[0022] The hot pressing pressure is 1-3 MPa and the time is 60-90 min.

[0023] The preparation method of the organic metal binder is:

[0024] H1: 3.2-6.4 parts of zirconium oxychloride, 100-200 parts of ethanol and 2.1-4.2 parts of 4,4'-divinyl-2,2'-bipyridine are mixed and added into a stirring kettle, heated to 30-50° C., and reacted for 100-150 minutes to obtain a divinyl-2,2'-bipyridine zirconium complex;

[0025] H2: Add 0.02-0.4 parts of allyl zinc bromide, 220-300 parts of polysilazane resin CAS: 475645-84-2, and 0.01-0.2 parts of 5-10% chloroplatinic acid isopropanol solution in a stirred kettle by weight, stir at 60-70° C. for 120-180 minutes, and the reaction is completed to obtain an organometallic polysilazane solution;

[0026] H3: According to weight, 20-32 parts of aluminum powder, 12-16 parts of silicon powder, and 5-11 parts of carbon powder are added to a ball mill and mixed and ground to obtain a mixed powder; the mixed powder and 10-17 parts of polysilazane resin are added to a container at the same time, stirred and prepared to obtain an organic metal binder.

[0027] The design concept of the organometallic binder in the present invention is:

[0028] The silicon-hydrogen bonds of the polysilazane resin undergo silicon-hydrogen addition reactions with the divinyl-2,2'-bipyridine zirconium complex and allyl zinc bromide, respectively, and then compounded with the mixed powder to obtain an organic metal binder.

[0029] The advantages and beneficial effects of the present invention are:

[0030] 1. The high thermal conductivity brake disc prepared by the present invention can effectively reduce SiO 2 The pores at the interface between the particles and the copper matrix improve the interface bonding state between the particles and the copper matrix; SiO 2 Copper plating on the particle surface can further improve the hardness and tensile strength of the composite material, and has good mechanical properties;

[0031] 2. The high thermal conductivity brake disc prepared by the present invention has a thermal conductivity of up to 143W / (m·K) at 300°C, greatly improved thermal conductivity, and has significant high thermal conductivity;

[0032] 3. The high thermal conductivity brake disc prepared by the present invention has high metal utilization rate, short manufacturing cycle and low production cost. DETAILED DESCRIPTION

[0033] The process is further described below in conjunction with implementation examples, but the present invention is not limited to these embodiments.

[0034] Example 1

[0035] A method for preparing a high thermal conductivity brake disc, the operating steps of which are:

[0036] S1: The pre-treated SiO 2The particles are placed in 15 kg of disodium ethylenediaminetetraacetate, 10 kg of formaldehyde, 10 kg of copper sulfate, 10 kg of potassium sodium tartrate, 10 kg of sodium hydroxide, and 100 kg of deionized water, and after heating, chemical electroplating is performed;

[0037] S2: Copper-plated SiO 2 The particles were placed in an ethanol solution, stirred for 30 min, then washed with the ethanol solution several times and dried;

[0038] S3: 70kg copper powder, 1kg copper-plated SiO 2 Particles, 1kg graphite, 3kg organic metal binder, mixed for 30 minutes, and then cold pressed using a flat vulcanizer;

[0039] S4: The cold pressed green sheet is sintered in a vacuum hot pressing furnace at high temperature, and then hot pressed and cooled to obtain a high thermal conductivity brake disc.

[0040] The electroplating temperature of S1 is 30°C.

[0041] The electroplating time of S1 is 10 minutes.

[0042] The copper plating thickness of S1 is 0.3 μm.

[0043] The SiO 2 The particle pretreatment steps are:

[0044] A1: Weigh 10kgSiO 2 The particles were repeatedly washed with distilled water, and then placed in 50 kg of acetone solution while soaking and stirring for 30 minutes; then placed in 50 kg of 10% HCl solution while soaking and stirring for 30 minutes; and then repeatedly washed with distilled water;

[0045] A2: SiO 2 The particles are then placed in 50 kg of 10% stannous chloride solution and stirred for 10 minutes; then they are repeatedly washed with distilled water;

[0046] A3: SiO 2 The particles are then placed in 50 kg of 0.1% palladium chloride solution, and stirred while soaking for 10 minutes; then washed repeatedly with distilled water; and dried for later use.

[0047] The stirring rate was 500 rpm.

[0048] The cold pressing process was performed at a pressure of 400 MPa and a time of 1 min.

[0049] The vacuum degree in the vacuum hot pressing sintering furnace is 1×10 -2 Pa, temperature is 800℃.

[0050] The hot pressing pressure is 1 MPa and the time is 60 min.

[0051] The preparation method of the organic metal binder is:

[0052] H1: 3.2 kg of zirconium oxychloride, 100 kg of ethanol and 2.1 kg of 4,4'-divinyl-2,2'-bipyridine were mixed and added into a stirred tank, heated to 30°C, and reacted for 100 minutes to obtain a divinyl-2,2'-bipyridine zirconium complex;

[0053] H2: Add 0.02 kg of allyl zinc bromide, 220 kg of polysilazane resin CAS: 475645-84-2, and 0.01 kg of 5% by mass chloroplatinic acid isopropanol solution into a stirring kettle, stir at 60° C. for 120 minutes, and the reaction is completed to obtain an organometallic polysilazane solution;

[0054] H3: 20 kg of aluminum powder, 12 kg of silicon powder, and 5 kg of carbon powder were added to a ball mill and mixed and ground to obtain a mixed powder; the mixed powder and 10 kg of polysilazane resin were added to a container at the same time, stirred, and an organic metal binder was obtained.

[0055] Example 2

[0056] A method for preparing a high thermal conductivity brake disc, the operating steps of which are:

[0057] S1: The pre-treated SiO 2 The particles are placed in 18 kg of disodium ethylenediaminetetraacetate, 12 kg of formaldehyde, 12 kg of copper sulfate, 14 kg of potassium sodium tartrate, 12 kg of sodium hydroxide, and 140 kg of deionized water, and after heating, chemical electroplating is performed;

[0058] S2: Copper-plated SiO 2 The particles were placed in an ethanol solution, stirred for 35 min, then washed with the ethanol solution several times and dried;

[0059] S3: 705kg copper powder, 2kg copper-plated SiO 2 Particles, 2kg graphite, 4kg organic metal binder, mixed for 40 minutes, and then cold pressed using a flat vulcanizer;

[0060] S4: The cold pressed green sheet is sintered in a vacuum hot pressing furnace at high temperature, and then hot pressed and cooled to obtain a high thermal conductivity brake disc.

[0061] The electroplating temperature of S1 is 35°C.

[0062] The electroplating time of S1 is 15 minutes.

[0063] The copper plating thickness of S1 is 0.4 μm.

[0064] The SiO 2 The particle pretreatment steps are:

[0065] A1: Weigh 14kgSiO 2 The particles were repeatedly washed with distilled water, and then placed in 60 kg of acetone solution while soaking and stirring for 50 minutes; then immersed in 60 kg of 15% HCl solution while soaking and stirring for 50 minutes; and then repeatedly washed with distilled water;

[0066] A2: SiO 2 The particles are then placed in 60 kg of 15% stannous chloride solution and stirred for 15 minutes; then they are repeatedly washed with distilled water;

[0067] A3: SiO 2 The particles are then placed in 60 kg of 0.2% palladium chloride solution, and stirred for 15 minutes while being immersed; then they are repeatedly washed with distilled water; and dried for later use.

[0068] The stirring rate was 600 rpm.

[0069] The cold pressing process was performed at a pressure of 450 MPa and a time of 2 min.

[0070] The vacuum degree in the vacuum hot pressing sintering furnace is 2×10 -2 Pa, the temperature is 850℃.

[0071] The hot pressing pressure is 2 MPa and the time is 70 min.

[0072] The preparation method of the organic metal binder is:

[0073] H1: 4.5 kg of zirconium oxychloride, 140 kg of ethanol and 3 kg of 4,4'-divinyl-2,2'-bipyridine were mixed and added into a stirred tank, heated to 35°C, and reacted for 110 minutes to obtain a divinyl-2,2'-bipyridine zirconium complex;

[0074] H2: Add 0.1 kg of allyl zinc bromide, 250 kg of polysilazane resin CAS: 475645-84-2, and 0.1 kg of 6% by mass chloroplatinic acid isopropanol solution into a stirring kettle, stir at 65° C. for 140 minutes, and the reaction is completed to obtain an organometallic polysilazane solution;

[0075] H3: 25 kg of aluminum powder, 13 kg of silicon powder, and 7 kg of carbon powder were added to a ball mill and mixed and ground to obtain a mixed powder; the mixed powder and 12 kg of polysilazane resin were added to a container at the same time, stirred, and an organic metal binder was obtained.

[0076] Example 3

[0077] A method for preparing a high thermal conductivity brake disc, the operating steps of which are:

[0078] S1: The pre-treated SiO 2 The particles are placed in 23 kg of disodium ethylenediaminetetraacetate, 14 kg of formaldehyde, 14 kg of copper sulfate, 18 kg of potassium sodium tartrate, 14 kg of sodium hydroxide, and 180 kg of deionized water, and after heating, chemical electroplating is performed;

[0079] S2: Copper-plated SiO 2 The particles were placed in an ethanol solution, stirred for 45 min, then washed with the ethanol solution several times and dried;

[0080] S3: 85kg copper powder, 4kg copper-plated SiO 2 Particles, 2kg graphite, 5kg organic metal binder, mixed for 55 minutes, and then cold pressed using a flat vulcanizer;

[0081] S4: The cold pressed green sheet is sintered in a vacuum hot pressing furnace at high temperature, and then hot pressed and cooled to obtain a high thermal conductivity brake disc.

[0082] The electroplating temperature of S1 is 45°C.

[0083] The electroplating time of S1 is 15 minutes.

[0084] The copper plating thickness of S1 is 0.4 μm.

[0085] The SiO 2 The particle pretreatment steps are:

[0086] A1: weigh 18kgSiO 2 The particles were repeatedly washed with distilled water, and then placed in 70 kg of acetone solution while soaking and stirring for 70 minutes; then immersed in 70 kg of 15% HCl solution while soaking and stirring for 70 minutes; and then repeatedly washed with distilled water;

[0087] A2: SiO 2 The particles are then placed in 70 kg of 15% stannous chloride solution and stirred for 25 minutes; then they are repeatedly washed with distilled water;

[0088] A3: SiO 2 The particles are then placed in 70 kg of 0.2% palladium chloride solution, and stirred while soaking for 25 minutes; then washed repeatedly with distilled water; and dried for later use.

[0089] The stirring rate was 900 rpm.

[0090] The cold pressing process was performed at a pressure of 450 MPa and a time of 2 min.

[0091] The vacuum degree in the vacuum hot pressing sintering furnace is 2×10 -2 Pa, the temperature is 950℃.

[0092] The hot pressing pressure is 2 MPa and the time is 80 min.

[0093] The preparation method of the organic metal binder is:

[0094] H1: 6 kg of zirconium oxychloride, 18 kg of ethanol and 4 kg of 4,4'-divinyl-2,2'-bipyridine were mixed and added into a stirred tank, heated to 45°C, and reacted for 140 minutes to obtain a divinyl-2,2'-bipyridine zirconium complex;

[0095] H2: Add 0.3 kg of allyl zinc bromide, 280 kg of polysilazane resin CAS: 475645-84-2, and 0.15 kg of 8% by mass chloroplatinic acid isopropanol solution into a stirring kettle, stir at 65° C. for 160 minutes, and the reaction is completed to obtain an organometallic polysilazane solution;

[0096] H3: 30 kg of aluminum powder, 15 kg of silicon powder, and 9 kg of carbon powder were added to a ball mill and mixed and ground to obtain a mixed powder; the mixed powder and 15 kg of polysilazane resin were added to a container at the same time, stirred, and an organic metal binder was obtained.

[0097] Example 4

[0098] A method for preparing a high thermal conductivity brake disc, the operating steps of which are:

[0099] S1: The pre-treated SiO 2 The particles are placed in 25 kg of disodium ethylenediaminetetraacetate, 15 kg of formaldehyde, 15 kg of copper sulfate, 20 kg of potassium sodium tartrate, 15 kg of sodium hydroxide, and 200 kg of deionized water, and after heating, chemical electroplating is performed;

[0100] S2: Copper-plated SiO 2 The particles were placed in an ethanol solution, stirred for 50 min, then washed with the ethanol solution several times and dried;

[0101] S3: 90kg copper powder, 5kg copper-plated SiO 2 The particles, 3kg graphite and 6kg organic metal binder were mixed for 60 minutes and then cold pressed using a flat vulcanizer.

[0102] S4: The cold pressed green sheet is sintered in a vacuum hot pressing furnace at high temperature, and then hot pressed and cooled to obtain a high thermal conductivity brake disc.

[0103] The electroplating temperature of S1 is 50°C.

[0104] The electroplating time of S1 is 20 minutes.

[0105] The copper plating thickness of S1 is 0.5 μm.

[0106] The SiO 2 The particle pretreatment steps are:

[0107] A1: weigh 20kgSiO 2 The particles were repeatedly washed with distilled water, and then placed in 80 kg of acetone solution while soaking and stirring for 90 minutes; then immersed in 80 kg of 20% HCl solution while soaking and stirring for 90 minutes; and then repeatedly washed with distilled water;

[0108] A2: SiO 2 The particles are then placed in 80 kg of 20% stannous chloride solution and stirred for 30 minutes; then they are repeatedly washed with distilled water;

[0109] A3: SiO 2 The particles are then placed in 80 kg of 0.3% palladium chloride solution, and stirred while soaking for 30 minutes; then washed repeatedly with distilled water; and dried for later use.

[0110] The stirring rate was 1000 rpm.

[0111] The cold pressing process was performed at a pressure of 500 MPa and a time of 3 minutes.

[0112] The vacuum degree in the vacuum hot pressing sintering furnace is 3X10 -2 Pa, temperature is 1000℃.

[0113] The hot pressing pressure is 3 MPa and the time is 90 min.

[0114] The preparation method of the organic metal binder is:

[0115] H1: 6.4 kg of zirconium oxychloride, 200 kg of ethanol and 4.2 kg of 4,4'-divinyl-2,2'-bipyridine were mixed and added into a stirred tank, heated to 50°C, and reacted for 150 minutes to obtain a divinyl-2,2'-bipyridine zirconium complex;

[0116] H2: Add 0.4 kg of allyl zinc bromide, 300 kg of polysilazane resin CAS: 475645-84-2, and 0.2 kg of 10% by mass chloroplatinic acid isopropanol solution into a stirring kettle, stir at 70° C. for 180 minutes, and the reaction is completed to obtain an organometallic polysilazane solution;

[0117] H3: 32 kg of aluminum powder, 16 kg of silicon powder, and 11 kg of carbon powder were added to a ball mill and mixed and ground to obtain a mixed powder; the mixed powder and 17 kg of polysilazane resin were added to a container at the same time, stirred, and an organic metal binder was obtained.

[0118] Comparative Example 1

[0119] No organic metal binder was added, and the rest was the same as in Example 1.

[0120] Comparative Example 2

[0121] No polysiloxane resin solution was added, and the rest was the same as in Example 1.

[0122] Comparative Example 3

[0123] Allyl zinc bromide was not added, and the other steps were the same as in Example 1.

[0124] Test method:

[0125] 1. Tensile properties are tested according to GB228;

[0126] 2. Brinell hardness is tested according to GB231;

[0127] 3. Use TCT416 thermal conductivity tester to test thermal conductivity.

[0128] Test results:

[0129]

[0130] Through the data analysis of the above embodiments and comparative examples, the high thermal conductivity brake disc prepared by the present invention has high hardness and tensile strength and has good mechanical properties; the high thermal conductivity brake disc prepared by the present invention has a thermal conductivity of up to 143W / (m·K) at 300°C and has significantly high thermal conductivity.

[0131] The above-described embodiments are merely descriptions of the technical solutions of the present invention, and the present invention is not limited by the above-described embodiments. Without departing from the design spirit and scope of the present invention, various improvements and changes to the present invention by those skilled in the art should all fall within the scope of the claims of the present invention.

Claims

1. A method for preparing a high thermal conductivity brake disc, characterized in that: The steps are: S1: Put the pretreated SiO2 particles into 15-25 parts of disodium ethylenediaminetetraacetate, 10-15 parts of formaldehyde, 10-15 parts of copper sulfate, 10-20 parts of potassium sodium tartrate, 10-15 parts of sodium hydroxide, and 100-200 parts of deionized water, and perform chemical plating after heating; S2: Place the copper-plated SiO2 particles in an ethanol solution, stir for 30-50 minutes, then wash with the ethanol solution several times and dry; S3: According to weight, 70-90 parts of copper powder, 1-5 parts of copper-plated SiO2 particles, 1-3 parts of graphite, and 3-6 parts of organic metal binder are mixed for 30-60 minutes, and then cold-pressed using a flat vulcanizer; S4: The pressed green body after cold pressing is sent to a vacuum hot pressing sintering furnace for high temperature sintering, followed by hot pressing and cooling to obtain a high thermal conductivity brake disc; The preparation method of the organic metal binder is: H1: 3.2-6.4 parts of zirconium oxychloride, 100-200 parts of ethanol and 2.1-4.2 parts of 4,4'-divinyl-2,2'-bipyridine are mixed and added into a stirring kettle, heated to 30-50° C., and reacted for 100-150 minutes to obtain a divinyl-2,2'-bipyridine zirconium complex; H2: Add 0.02-0.4 parts of allyl zinc bromide, 220-300 parts of polysilazane resin CAS: 475645-84-2, and 0.01-0.2 parts of 5-10% by weight chloroplatinic acid isopropanol solution into a stirred kettle, stir at 60-70° C. for 120-180 minutes, and the reaction is completed to obtain an organometallic polysilazane solution; H3: According to weight, 20-32 parts of aluminum powder, 12-16 parts of silicon powder, and 5-11 parts of carbon powder are added to a ball mill and mixed and ground to prepare a mixed powder; the mixed powder and 10-17 parts of organometallic polysilazane are added to a container at the same time, stirred and prepared to obtain an organometallic binder.

2. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The chemical plating temperature of S1 is 30-50°C.

3. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The chemical plating time of S1 is 10-20 minutes.

4. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The copper plating thickness of S1 is 0.3-0.5 μm.

5. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The SiO2 particle pretreatment steps are: A1: Weigh 10-20 parts of SiO2 particles by weight, wash them repeatedly with distilled water, and then soak them in 50-80 parts of acetone solution while stirring for 30-90 minutes; then soak them in 50-80 parts of 10-20% HCl solution while stirring for 30-90 minutes; then wash them repeatedly with distilled water; A2: Place the SiO2 particles into 50-80 parts of 10-20% stannous chloride solution, and stir while soaking for 10-30 minutes; then wash repeatedly with distilled water; A3: Place the SiO2 particles into 50-80 parts of 0.1-0.3% palladium chloride solution, and stir while soaking for 10-30 minutes; then wash repeatedly with distilled water; and dry for later use.

6. The method for preparing a high thermal conductivity brake disc according to claim 5, characterized in that: The stirring rate is 500-1000 rpm.

7. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The cold pressing pressure is 400-500 MPa and the time is 1-3 min.

8. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The vacuum degree in the vacuum hot pressing sintering furnace is 1×10 -2 ~3×10 -2 Pa, temperature is 800-1000℃.

9. The method for preparing a high thermal conductivity brake disc according to claim 1, characterized in that: The hot pressing pressure is 1-3 MPa and the time is 60-90 min.

Citation Information

Patent Citations

  • High-thermal-conductivity brake disc and preparation method thereof

    CN116287960A

  • Manufacturing process of high-performance titanium brake disc blank

    CN116551316A

  • Brake disc with good heat dissipation function

    CN219413340U

  • Methods for fabricating shapes by use of organometallic, ceramic precursor binders

    US5641817A